Belief as a Cognitive and Practical Commitment - Djigo, Sophie (ETHICS IN PROGRESS, 2013)
Exploring the idea of a more practical relationship between the agent and his own mental life leaves room for reconsidering the relevance of the familiar analogy between reasons for belief and reasons for action. Even if their difference is usually admitted, they are also treated as equivalent, in the sense that the connection between reasons to believe and the arising belief would be analogous to the connection between reasons for action and the arising action. If such an analogy might be relevant to a certain extent in the frame of a theoretical stance towards oneself, I'll argue that it cannot be maintained once we have put the agent at the heart of self-knowledge.